Instability of nonminimally coupled scalar fields in the spacetime of thin charged shells - Santiago, Jessica; Landulfo, Andre G. S.; Lima, William C. C.; Matsas, George E. A. [UNESP]; Mendes, Raissa F. P.; Vanzella, Daniel A. T. (Amer Physical Soc, 2016)
We investigate the stability of a free scalar field nonminimally coupled to gravity under linear perturbations in the spacetime of a charged spherical shell. Our analysis is performed in the context of quantum field theory in curved spacetimes. This paper completes previous analyses which considered the exponential enhancement of vacuum fluctuations in the spacetime of massive shells.